92.6k views
0 votes
How do you solve it to get the answer to this problem

How do you solve it to get the answer to this problem-example-1

1 Answer

5 votes
The first equation is solved for x.
We can use the substitution method and substitute for x in the second equation.

x = 3y
3x - 5y = 12

3(3y) - 5y = 12

9y - 5y = 12

4y = 12

y = 3

Now that we know y, we substitute in the first original equation to find x.

x = 3y

x = 3(3)

x = 9

Answer: x = 9 and y = 3
User Felix Marianayagam
by
5.7k points